The Students’ Perception of YouTube in Learning English to Improve Speaking Skills on Senior High School in Eleven Grade (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study explores the perceptions of 11th-grade students at SMAIT Annur Bekasi regarding the use of YouTube in learning English to improve speaking skills. This research employs a descriptive qualitative method with a narrative approach to collect data from 10 purposively selected students. Data were gathered through semi-structured interviews in the participants' natural environment. The findings indicate that YouTube can be an effective tool for enhancing students' English speaking skills through diverse and engaging content, providing opportunities for practice and feedback. Students reported that watching YouTube videos helped them understand more natural pronunciation, intonation, and expressions in English. Additionally, the use of subtitles and participation in discussions in the comment sections also contributed to their skill improvement. This study highlights the importance of integrating digital platforms like YouTube in language learning to create a more enjoyable and effective learning experience for students?.